2021
DOI: 10.1093/mr/roab109
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis is a risk factor for refracture in patients with fragility fractures

Abstract: Objectives To determine whether patients with rheumatoid arthritis (RA) who have had fragility fractures are at an increased risk of refractures. Methods Patients with fragility fractures who were treated surgically at ten hospitals from 2008 to 2017 and who underwent follow-up for more than 24 months were either categorized into a group comprising patients with RA or a group comprising patients without RA (controls). The gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Feature importance in our study showed the several potential predictors for clinical refractures, which can be divided into two groups. First, a group contained the items already detected by previous reports [ 9 , 28 ]. RA and no post-operative treatments for osteoporosis correspond to this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Feature importance in our study showed the several potential predictors for clinical refractures, which can be divided into two groups. First, a group contained the items already detected by previous reports [ 9 , 28 ]. RA and no post-operative treatments for osteoporosis correspond to this.…”
Section: Discussionmentioning
confidence: 99%
“…RA was also detected as a relevant feature for clinical refracture, and RA is known to be a risk factor for refracture as well as fracture [ 7 , 9 ]. Osteoclasts are the main cell population responsible for bone loss in patients with RA [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation